Analysis on the medication rule of traditional Chinese medicine in the treatment of COVID-19 patients. Issue 2 (17th June 2022) - Tan, Xiaoyu; Yang, Qingqing; Cai, Xianming; Tao, Yiming; Gao, Suyu; He, Lixia; Zhao, Yubin; Zhan, Siyan; Cheng, Hong; Song, Haibo; Sun, Feng
Abstract: Objective: To describe patterns of utilization of traditional Chinese medicine (TCM) in the treatment of patients with coronavirus disease 2019 (COVID-19). Methods: Adult patients with COVID-19 who received TCM treatment were divided into a non-serious group (mild and moderate types) and a serious group (severe and critical types) according to their admission conditions. The medical records and prescriptions of these patients were investigated to determine their TCM utilization patterns. Results: In all, 3, 872 COVID-19 patients were included. Oral Chinese traditional patent medicine (CPM) was the most commonly used type of TCM, followed by decoction. The proportion of multi-drug combinations was higher than single drug use (55.0% vs. 45.0%). Decoction combined with oral CPM was the most common combination (39.1%, 1, 514/3, 872). Orally administered, injected, and externally applied CPM were significantly more common in the serious group than in the non-serious, while decoction and non-drug TCM treatments were more common in the non-serious than in the serious group. Multi-drug combinations were used for the majority of patients in both groups, mainly in the form of decoctions combined with oral CPM. Among the serious patients, injected CPM was more often used in patients who died during treatment (35.0%, 36/103). The two most common medication patterns were decoction combined with oral CPM and oral CPM alone in the two finally discharged groups. Oral CPM alone or used in combination with injected CPM were seen most commonly in the death group. Significant differences were established in TCM utilization and medication patterns among patients in three groups who had different prognoses and outcomes. Conclusions: The treatment measures and medication patterns of TCM commonly used in COVID-19 patients with the range of conditions found in this study should be further explored in the future to provide a more complete reference for COVID-19 treatment.